1993
DOI: 10.1093/rheumatology/32.5.362
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Dna Antibodies in the Primary Antiphospholipid Syndrome (Paps)

Abstract: Primary antiphospholipid syndrome (PAPS) is considered a distinct entity from SLE and patients with PAPS are generally regarded as being dsDNA antibody negative. Levels of IgG and IgM ss and ds DNA antibodies were measured by ELISA in 30 patients who fulfilled the criteria for the diagnosis of PAPS. We compared these patients with 20 normal controls and seven patients with idiopathic SLE. We also examined all the sera for anti-nuclear antibodies by Hep-2 cells and for dsDNA antibodies by Crithidia. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…As discussed above about plasma levels of sRAGE, there was no good explanation for such findings. Although not often examined in pAPS patients, some studies indicated that the production of autoantibodies is prevalent in pAPS patients [31,32]. Interestingly, we observed a poor correlation between plasma levels of HMGB1 measured by ELISA and Western blot.…”
Section: Discussioncontrasting
confidence: 68%
“…As discussed above about plasma levels of sRAGE, there was no good explanation for such findings. Although not often examined in pAPS patients, some studies indicated that the production of autoantibodies is prevalent in pAPS patients [31,32]. Interestingly, we observed a poor correlation between plasma levels of HMGB1 measured by ELISA and Western blot.…”
Section: Discussioncontrasting
confidence: 68%
“…To coat dsDNA, calf thymus dsDNA was adsorbed to a 96-well ELISA plate precoated with poly- l -lysine (50 μg/ml) at 4°C overnight [41]. After charge neutralizing the plates with poly- l -glutamate (100 μg/ml in distilled water), the plates were blocked with 2% casein (37°C, 1 h for each step).…”
Section: Methodsmentioning
confidence: 99%
“…Anti‐DNA antibodies have been reported in patients with a variety of rheumatologic diseases and other conditions including: rheumatoid arthritis, Sjögren's syndrome, scleroderma, drug induced lupus, Raynaud's phenomenon, mixed connective tissue disease, discoid lupus, myositis, chronic active hepatitis, other liver diseases, uveitis, relatives of SLE patients, patients hospitalized for nonrheumatologic diseases, Graves' disease, Alzheimer's disease, juvenile rheumatoid arthritis, certain laboratory workers, anticardiolipin antibody syndrome, and persons with silicone breast implants (41–60). The frequency of elevated levels of anti‐DNA antibodies in conditions other than SLE is uniformly low (≤5% of patients), and when present, they are often present in low titer.…”
Section: Indications For Clinical Use Of the Anti‐dna Antibody Testmentioning
confidence: 99%